Community Partnership Program (PKM) Research Statistics for Teachers in NU Plus Vocational School, Sidoarjo - Edy Widayat; Ardianik Ardianik; Sucipto Sucipto (OJS Universitas Muhammadiyah Gresik, 2019)
The NU PLUS vocational school (SMK) located in Sidoarjo Regency as a forum for nation generation, always applies various methods and development of learning media to answer the demands of the era to produce high-quality human resources, the problem facing this school is that the ability of teachers is still lacking in analyzing research data using statistical tests. Therefore, it is necessary to increase human resources concerning research through data analysis training. One way to help teach teachers in conducting research is to provide training in research data analysis using SPSS software. SPSS software is a software that can help process research data making it easier for researchers to analyze the data. This training aims to solve the problems faced by Sidoarjo Vocational High School teachers as partners, by providing training and mentoring methods of data analysis which include: 1) Methods of data analysis using descriptive statistics; 2) Methods of Quantitative data analysis using parametric statistics; 3) Qualitative Data Analysis Method using non-parametric statistics; 4) Research Methods, Classroom Action Research. The training design above is expected to improve some of the abilities and skills of the Sidoarjo Vocational High School teachers, including the following: 1) Processing research data using descriptive statistics; 2) Quantitative data processing using parametric statistics; 3) Processing of qualitative data using non-parametric statistics; 4) Mastering Research methods with Quantitative and Qualitative Approaches; 5) Able to carry out Classroom Action Research. The expected target of the community service activities in Sidoarjo Plus Vocational School includes: 1) Increased understanding, ability, and skills in analyzing data using descriptive statistics; 2) Increasing understanding, ability and skills in analyzing quantitative data by utilizing various kinds of parametric statistical tests that are tailored to the problem; 3) Improve understanding, ability and skills in analyzing qualitative data by utilizing various kinds of non-parametric statistical tests that are tailored to the problem; 4) Training manual; 5) Certificates and posters; 6) Scientific Publication in the Journal